DETERMINAN PENERAPAN HIGIENE SANITASI MAKANAN PADA PEDAGANG ANGKRINGAN SELAMA MASA PANDEMI COVID-19 - Dyah Suryani; Arihni Arihatal Jannah (Universitas Pahlawan, 2021)
The Covid-19 pandemic is still not over, although there is no valid data but there are allegations that this virus has the potential to transmit through food and food packaging. Angkringan is a place to sell snack food, so it is important angkringan traders apply hygiene food sanitation to prevent this possibility. The factors that drive such actions are education, knowledge, attitudes, infrastructure facilities, training, income and working life. The purpose of this study is to find out the relationship between education, knowledge, attitudes, infrastructure facilities, training, income, working life with the application of food sanitation hygiene to angkringan traders during the Covid-19 pandemic in Kelurahan Warungboto , Umbulharjo, Yogyakarta. Quantitative research uses analytical observational methods with cross sectional design. The number of samples as many as 35 traders angkringan with the technique of totaly sampling. Data analysis using fisher's exact CI test of 95% (Î± = 0.05). There is a knowledge level relationship with the application of food sanitary hygiene (p-value=0.007). There is a knowledge level relationship with the application of hygiene to food sanitation (p-value = 0.000). There is no attitude relationship with the application of hygiene sanitation of food (p-value = 0.155). There is a relationship between infrastructure facilities and the application of hygiene sanitation of food (p-value = 0.006). There is no training relationship with the application of hygiene sanitation of food (p-value = 1,000). There is no income relationship with the application of food sanitary hygiene (p-value = 0.151). There is a working relationship with the application of hygiene sanitation of food (p-value = 0.003). There is a relationship of education, knowledge, infrastructure and working period with the application of hygiene sanitation of food to angkringan traders. There is no relationship between attitude, participation in training and income with the application of hygiene sanitation of food to angkringan traders.